INTERNALISASI NILAI-NILAI MUJAHADAH PEMBACAAN SURAT PILIHAN DALAM PEMBENTUKAN KARAKTER QUR’ANI SANTRI DI PONDOK PESANTREN ASY-SYUJAA’IYYAH WONOSOBO: STUDI LIVING QUR’AN - -, Misyono; Mubin, Nurul; Muntaha, Darul (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2024)
The aim of this study is to analyze the internalization of the values of mujahadah in reading selected surahs in the formation of the Qur'anic character of students at the Asy-Syujaa'iyyah Wonosobo Islamic Boarding School: A Study of the Living Qur'an. This field research is a qualitative research method using a phenomenological approach. Data was collected through observation, interviews, and documentation, which were then analyzed qualitatively through the stages of data reduction, data presentation, and verification/conclusion drawing. The findings confirm that the values embodied in the mujahadah (recitation of selected surahs) include educational values, the values of monotheism, and the values of 'ubudiyah (obedience). Mujahadah encourages students to internalize these values and implement them diligently in their daily Quran-based activities. This spirit is not only about understanding Quranic character concepts, but also about direct experience in creating a positive impact in the community. This research provides new insights into the students' commitment to self-control in relation to the values of a religious ritual and the promotion of spiritual well-being through the practice of Quranic mujahadah.